ORGANIZING OF ACCOUNTING AND TAXATION OF EXPORT-IMPORT OPERATIONS OF AN ENTERPRISE UNDER THE CONDITIONS OF THREATS TO UKRAINE’S ECONOMIC SECURITY - Maletska , O.I. (The actual problems of regional economy development, 2025)
The article explores the specific features of organizing accounting for foreign economic activity (FEA) in a business entity under the conditions of threats to Ukraine's economic security. Particular attention is given to the interrelation between accounting and tax regulation of export-import operations. It is noted that current threats to economic security require a higher level of reliability in accounting information and a rapid adaptation of accounting policies to changes in currency, customs, and tax legislation. Using the example of LLC “Teсnoсap UA”, the paper analyzes practical aspects of accounting for FEA. The company carries out export deliveries to the Czech Republic and Spain, indicating its active participation in international trade. The study examines primary documents that are crucial for both accounting and tax credit purposes, including customs declarations, acceptance certificates, consignment notes, and tax invoices. It is established that the registration of tax invoices in the Unified Register of Tax Invoices (URTI) prior to submitting the customs declaration is a mandatory condition for applying the zero VAT rate. Special attention is paid to the accounting of import operations accompanied by VAT accrual upon importing goods into the customs territory of Ukraine. It is shown that the customs value, which includes related expenses (transportation, insurance, customs duties), forms the basis for recording assets, expenses, and tax credit. The study finds that effective organization of FEA accounting in an unstable environment requires close integration with tax administration. Accounting processes must ensure a reliable information base for the timely fulfillment of tax obligations and compliance with currency regulations, particularly regarding contract settlement deadlines and the procedure for selling foreign currency earnings. The scientific novelty of the study lies in a comprehensive approach to analyzing the practical experience of organizing FEA accounting at an enterprise under threats to Ukraine’s economic security. This allows for the formulation of proposals to improve accounting discipline, reduce tax risks, and ensure transparency in foreign economic activity. The practical significance of the research lies in the possibility of applying the obtained results to improve the accounting policy of enterprises operating in international markets, taking into account modern economic challenges.Key words: export, import, foreign economic activity, accounting, currency transactions, tax obligations, martial law, documentation.